Sustainable Service Innovation and Financial Resilience to Strengthen Business in the Era of Economic Shocks - Bayu Ilham Pradana; Syahbandi Syahbandi (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Economic volatility in emerging markets presents significant challenges for businesses, small and medium enterprises, in maintaining operational stability and competitiveness. This study aims to explore how sustainable service innovation and financial resilience strategies enable businesses to effectively navigate economic disruptions. A qualitative approach was employed, utilizing a systematic literature review of academic journals, books, and industry reports published between 2019 and 2025. The findings reveal that digital platforms and eco-friendly service models enhance customer retention and operational efficiency, while diversified revenue streams and inclusive finance bolster financial stability during times of crisis. Adaptive leadership and strategic collaborations with stakeholders, including government and regional partners, further strengthen resilience by facilitating the sharing of resources and innovation. The study concludes that integrating sustainable service innovation, robust financial strategies, and collaborative leadership enables businesses to achieve sustainable transformation in volatile economic environments. These insights underscore the importance of aligning business practices with sustainability and stakeholder engagement to ensure long-term competitiveness, providing valuable guidance for small and medium-sized enterprises and policymakers in emerging economies.